Serial Multiple Mediation of Professional Identity, and Psychological Capital in the Relationship Between Work-Related Stress and Work-Related Well-Being of ICU Nurses in China: A Cross-Sectional Questionnaire Survey - Hao, Cuiping; Zhu, Lina; Zhang, Suzhen; Rong, Shan; Zhang, Yaqing; Ye, Jiuhang; Yang, Fuguo (Frontiers in Psychology, 2020)
ABSTRACT This study aimed to investigate the serial-multiple mediation effect of professional identity, psychological capital (PsyCap), work-related stress, and work-related well-being among intensive care unit (ICU) nurses in China. The cross-sectional survey was conducted from January 2017 to May 2017 in two Grade III A general hospitals (with more than 2000 beds) in Jining, Shandong Province, China. Cluster sampling was used to recruit participants from the two hospitals. A total of 330 ICU nurses participated in the study. The Nurses’ Work Stress Scale, Chinese Nurse’s Professional Identity Scale, the PsyCap Questionnaire, and Chinese Work-related Well-being Scale were used to collect the data. Descriptive analysis, independent-samples t test, one-way analysis of variance, Pearson correlation analysis, linear regression analysis, and structural equation modelling were used to analyse the data.（P < 0.05 was considered statistically significant）.The average score for the work-related well-being of ICU nurses was 85.91 ± 13.94. Work-related stress, professional identity, and PsyCap correlated significantly with work-related well-being. The major predictors of work-related well-being were PsyCap, work-related stress, professional identity, and monthly salary. The serial-multiple mediation effects of professional identity and PsyCap in the relationship between work-related stress and work-related well-being were statistically significant. Positive professional identity and PsyCap were sequentially associated with decreased work-related stress, which in turn was related to increased work-related well-being among ICU nurses. Keywords: Professional identity, psychological capital, serial-multiple mediation model, work-related stress, work-related well-being